Heterogeneous Beliefs and the Effect of Replicatable Options on Asset Prices - Kraus, Alan; Smith, Maxwell (Review of Financial Studies, 1996)
We present two ways in which trading in a replicatable option can affect the price process of the underlying asset. In the first situation, trading an option that each investor views as pay off redundant breaks a non-fully revealing equilibrium that exists when the option market is absent. The second situation involves a market that is dynamically complete without options, but in which introducing an option market allows self-confirming conjectures of additional uncertainty about the future price of the underlying asset. Heterogeneous beliefs play important though different roles in both situations.